Diagnostic and Prognostic Values of Cardiopulmonary Exercise Testing in Cardiac Amyloidosis - Rishika Banydeen; Rishika Banydeen; Astrid Monfort; Astrid Monfort; Jocelyn Inamo; Jocelyn Inamo; Remi Neviere; Remi Neviere (Frontiers in Cardiovascular Medicine, 2022)
Cardiac amyloidosis (CA) is a myocardial disease characterized by extracellular amyloid infiltration throughout the heart, resulting in increased myocardial stiffness, and restrictive heart wall chamber behavior. Its diagnosis among patients hospitalized for cardiovascular diseases is becoming increasingly frequent, suggesting improved disease awareness, and higher diagnostic capacities. One predominant functional manifestation of patients with CA is exercise intolerance, objectified by reduced peak oxygen uptake (VO2 peak), and assessed by metabolic cart during cardiopulmonary exercise testing (CPET). Hemodynamic adaptation to exercise in patients with CA is characterized by low myocardial contractile reserve and impaired myocardial efficiency. Rapid shallow breathing and hyperventilation, in the absence of ventilatory limitation, are also typically observed in response to exercise. Ventilatory inefficiency is further suggested by an increased VE-VCO2 slope, which has been attributed to excessive sympathoexcitation and a high physiological dead space (VD/VT) ratio during exercise. Growing evidence now suggests that, in addition to well-established biomarker risk models, a reduced VO2 peak is potentially a strong and independent predictive factor of adverse patient outcomes, both for monoclonal immunoglobulin light chain (AL) or transthyretin (ATTR) CA. Besides generating prognostic information, CPET can be used for the evaluation of the impact of therapeutic interventions in patients with CA.